(untitled) (Bangladesh Journal of Agricultural Research, 2016)
An experiment was carried out in 6x6 diallel crosses for combining ability analysis for grain yield, maturity and growth parameters in maize. Analysis of variance for combining ability showed that mean square value due to GCA & SCA were highly significant for all characters except SCA in days to tasseling and days to maturity indicated that all but two traits were governed by both additive and non-additive gene action. Variances due to GCA were much higher in magnitude than SCA indicated additive gene effects were much more important for all characters except cob length, thousand grain weight and ear height. The Parent P5 was the best general combiner for yield and most of the yield contributing characters. The Parent P1 & P2 were best general combiner for both dwarf and earliness. The crosses showing significant SCA effects for yield involving average x average, average x low and low x low general combining parents. The crosses P3xP6 & P4xP5 showed either significantly or numerically higher heterosis than checks BHM-5, BHM- 7 & BHM-9 for yield. Bangladesh J. Agril. Res. 41(2): 365-376, June 2016